PENGARUH WAKTU APLIKASI PUPUK HAYATI VP3 BERSAMA KOMPOS DIBANDINGKAN DENGAN EM4 DAN PUPUK NPK TEHADAP PRODUKSI DAN KUALITAS TANAMAN BAYAM HIJAU (Amaranthus tricolor L.) - nurlailah nurlailah (AGRONISMA, 2020)
AbstractVP3 biological fertilizer that has been formulated and developed in previous studies contains 3 soil bacteria, namely N free-fixing bacteria, phosphate solvent bacteria and EPS-producing bacteria (exopolysaccharides) and the production of green spinach is unknown. Em4 is a culture solution (culture) of microorganisms that live naturally in fertile soil and is useful for increasing production. VP3 biological fertilizer applied with compost can be used to degrade compost into humus (fine particles / colloids) which play an important role for microorganisms, soil and plants when adapted to the application. The design used was randomized block design (RBD) with 7 treatments 3 replications. The provision of VP3 biological fertilizer and compost incubated 1 week before planting and applied when planting gives the best results on the quality of green spinach on the shelf life test.